Towards a pro-poor agricultural growth strategy in Nigeria - Fan, Shenggen; Omilola, Babatunde; Rhoe, Valerie; Salau, Sheu (International Food Policy Research Institute, 2008)
Agriculture remains a major sector for the Nigerian economy. The majority of Nigerians rely on agriculture for their livelihood. It is increasingly evident that improved agricultural development and growth can offer a pathway from poverty, but evidence-based policies and strategies are needed. Nigeria's agricultural policies have been inconsistent, uncoordinated and ad hoc. Such agricultural policies have limited the realization of the sector's full potential. A paradigm shift towards a sound evidence-based policymaking process is needed to promote a more equitable, gender sensitive and environmentally sustainable growth in the agricultural sector. The recent food price surge has made this paradigm shift even more important. This brief overviews the recent performance of agriculture in Nigeria, reviews past key agricultural policies and strategies, and explores future options in promoting further agricultural growth. --Authors' Abstract